Implementasi Regulasi Kepariwisataan Berbasis Harmonisasi Hukum Adat Lokal untuk Kesejahteraan Masyarakat (Studi Sosio- Legal Masyakarat Adat Suku Sasak di Batu Layar, Lombok Barat) - Rahman, Irham; Putra, Restu Adi (UNES Law Review, 2023)
The tourism sector has an important role for the country, one of which is a source of foreign exchange from tourists as state income. Apart from that, the tourism industry can encourage regional and national economic growth. One area that has potential as a tourist attraction is West Lombok Regency, West Nusa Tenggara Province. The authority of the regional government as implementer of regional regulations, namely West Lombok Regency Regional Regulation Number 6 of 2016 concerning the Master Plan for Regional Tourism Development for 2016-2025, must maximize tourism policies for tourism progress. However, the people of West Lombok, Batu Layar, are the Sasak tribe who have inherent traditions and customs and culture that must be maintained. The problem faced by the government is that there is a legal gap between regional regulations for tourism development and local indigenous communities. This type of research uses empirical research methods, namely examining the application of existing laws in society. The results of this research are that the implementation of regulations from regional governments in tourism development experiences obstacles, namely misunderstandings in the interpretation of policies by villages, and clashes between indigenous communities and regional governments.